JOINT LIFE DALAM ASURANSI JIWA BERJANGKA - Dini Hidayati; Dewi Anggraini; Dewi Sri Susanti (EPSILON: JURNAL MATEMATIKA MURNI DAN TERAPAN, 2015)
Generally in life insurance apply the condition of single life and joint life. Single life condition on life insurance is a condition when someone who wants to buy an insurance policy only for himself, meaning that can not be replaced by other people or parties. While the condition of joint life is a condition when two or more people who want to buy an insurance policy. For example husbands, wives, parents, and children, so there is dependence between policyholders either in joint opportunities, the sum insured, or premium payments. This study aims to determine the form of life and death opportunities for 3 policyholders, and joint life formulation in term and term life insurance. This research is a literature study, ie researchers collect materials or materials related to the research topic. Then study and re-explain the concept by applying it to the sample problem. The results of this study indicate that the chances of life and death for 3 people policyholders shaped mxyznp = () Σ = 3miixyznp. The term life joint annuity depends on the chance of living together and certain interest in the form of: xyzna = Σ - = ++ 1011ntxyzttpv and: xyzna = Σ- = 10ntxyzttpv. Insurance joint life futures depend on the chance of dead together and a particular interest in the form of 1: xyznA = Σ - = + 101ntxyzttqv.